Development of international trade and use of biofuels - Falkelius, Christian (2006)
The international trade and use of biofuels is rapidly increasing all over the world, and it is projected to continue the next years according to conclusions in this report. The main reasons are a global increased demand of energy, an increased awareness and knowledge of the environment, and the fact that conventional energy resources are running dry. Traditionally, has biofuels been produced and used within the same geographical region. This has however started to change due to an increased international demand. Consumption, production and trade do however differ between countries due to different conditions for production and consumption of biofuels.